PENGARUH KEPEMIMPINAN, KEDISIPLINAN, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN BPU ROSALIA INDAH KARANGANYAR - Purnamasari, Titik (Universitas Slamet Riyadi, 2015)
This study was a survey done to BPU Rosalia Indah Karanganyar employee, aims to find out the effect of leadership, discipline, and organization comitment on the employee performance. The research sample comprised 122 employees. The sample taking technique used proportional clustered random sampling by proportional 30 percent each division. The data were collected trough direct observation and questioner. They were analyzed using the multiple regression technique. There is significant effect of the leadership on the BPU Rosalia Indah Karanganyar employee performance and the leadership giving most dominant effect on the employee performance; there is significant effect of the discipline on the BPU Rosalia Indah Karanganyar employee performance; and there is significant effect of the organization commitment on the BPU Rosalia Indah Karanganyar employee performance. The leadership, discipline and organization commitment rate variables give a contribution of 42,3 percent. Keywords: leadership, discipline, organization commitment, employee performance